JOURNEY WOMEN: WOMEN’S RESILIENCE AND TRANSFORMATION IN QASHAM BALATA’S RUNAWAY TO NOWHERE - Hassan, Lolav M. (Journal of Duhok University, 2018)
This study explores the developmental processes of a number of female characters in Qasham Balata’s Runaway to Nowhere (2010) which depicts the implications of a series of historical incidents on Kurdish women’s experiences as expressive of the collective Kurdish socio-political experience in Iraq. Writing from a feminist perspective, Balata focuses on the maturation of Nareen, the protagonist, and portrays her transformation from a hopeless victim to a well-informed social activist. By cataloguing the experiences of Nareen and other female characters in the period immediately before and during the Persian Gulf War 1990-1991, the Kurdish popular Uprising, the Kurds’ subsequent mass-exodus to the Turkish and Iranian borders, and the creation of a de-facto Kurdish state in the north of Iraq, Balata shows that such destructive events represent shifting phases in the maturation processes of the lives of Kurdish women who learn how to survive these events and aspire to make a positive change, at least on personal levels. In the exploration of Nareen’s determination as well as her resilience and eventual emancipation, Rita Felski’s argument of modern writing by women as a medium through which female political identities and collective consciousness are constructed and represented are adopted to discuss the structural and thematic properties of the text.